Sacred Vaulted South: Proposing GIS-powered vaults cluster analysis and cultural itineraries into religious heritage buildings - Pacheco, M.; Flor, A. P. F.; Volzone, R. (CIDADES, Comunidades e Territórios, 2025)
In the south of Portugal, brick vaults are a particular traditional building system for ceilings, floors and terraces, using local materials and techniques, presently viewed as an example of sustainable construction. It was applied in various building typologies, from dwellings to religious buildings (churches, chapels, monasteries and convents), ranging from erudite to popular contexts. Vaulted buildings carry material and immaterial values related to traditional craftsmanship, knowledge transmission and religious practices, with heritage value and the potential to be a target of fruition by local people and visitors, playing an important role in the regeneration of the hinterland areas. This paper aims to present the potential of vernacular vaulted religious buildings to foster a sustainable territorial development empowered using digital tools in cultural tourism, promoting their understanding, dissemination and exploration among academic experts and the general public, as well as to reinforce the need for their further recovery, use and reuse. This study was conducted under the scope of the research project Vaulted South – Vernacular vaulted houses in south of Portugal, focusing on an inner sub-region of Southern Portugal, Baixo Alentejo, and it is based on the data collected during the census of vaulted buildings settled in the regions of Portel, Moura and Serpa, as pilot case studies. Georeferenced data were handled into a GIS environment for statistical analysis and the development of thematic itineraries. First results promoted a deeper knowledge about vaulted buildings and the creation, transfer and discussion of their potential knowledge and cultural values.